Удосконалення конструкції підводних населених апаратів теплоізолюючими блоками плавучості = The improvement the design of manned submersibles by use of thermal insulating buoyancy blocks - Юреско, Т. А.; Yuresko, T. A. (My University, 2020)
У дисертації обґрунтовано напрямок удосконалення конструкції підводного населеного апарату (ПНА) теплоізолюючими блоками зі сферопластика з додатковою поруватістю (СДП) з глибиною експлуатації 1500…2000 м. = The thesis covers the problem of improvement the design of manned submersibles by installation buoyancy blocks with syntactic foam with additional porosity (SFAP). Damage accumulation in SFAP blocks was experimentally studied during prolonged dives of the underwater-inhabited device under different depths and under cyclic dive-surfacing for air temperatures below 0ºC.
Юреско, Т. А. Удосконалення конструкції підводних населених апаратів теплоізолюючими блоками плавучості : автореф. дис. ... канд. техн. наук : 05.08.03 / Т. А. Юреско ; МОН України, НУК ім. адмірала Макарова ; наук. керівник Є. Т. Бурдун. - Миколаїв, 2017. – 23 с. + електрон. копія
Keywords: підводний населений апарат; конструкція; блоки плавучості; пошкоджуваність; сферопластик з додатковою поруватістю; гідростатичний тиск; кліматичний фактор; manned submersible; design; buoyancy blocks; damaging; syntactic foam of additional porosity; hydrostatical pressure; climatic factor